Soil Salinity, Infiltration and Organic Matter Status under Different Landforms in Coastal West Bengal - RAUT, SHISHIR; SARANGI, S K; LAMA, T D (Journal of the Indian Society of Coastal Agricultural Research, 2019)
Sorptivity was determined from soils of three different landforms, namely, non-cultivated deltaic (NCD), mud flat (MUD) and depressed low land (DL) under Gosaba Block of coastal West Bengal. The area covers approximately 4 km2 and soil samples were collected during the dry season (Feb. - March) of 2018. A horizontal infiltration study was carried out in the laboratory in plexiglass columns packed with soil for determining the infiltration and sorptivity parameters. Physicochemical parameters like pH2, EC2, saturated moisture content, texture, organic C were determined. The humic components of organic matter, namely, humic acid and fulvic acid, were also separated out to study their effect, if any, on soil sorptivity. Steady state cumulative infiltration was the highest (50-55 mm) in NCD soil and lowest (18-20 mm) in DL soil. The highest sorptivity of 3.1-3.5 mm min-Â½ was found in NCD soil and lowest in DL soil (1.0-1.1 mm min-1/2). Organic C content of all soils were medium to high (0.50-1.20%) and EC2 values were also low (< 4 dS m-1) in most of the soils except DL soil which had an EC2 value of 4-5.8 dS m-1. Saturated moisture content was highest in DL soil. The NCD soils contained higher fraction of fulvic acid (0.10-0.12%) which enhanced infiltration, whereas DL soils contained greater fraction of insoluble humic acid (0.27-0.31%) and exhibited less cumulative infiltration. MUD soils showed intermediate values. The relationships between sorptivity and clay, pH, EC, porosity and humic acid were significant (r = -0.90, -0.86, -0.86, -0.87 and -0.90, respectively), exponential and negative. Percentage fulvic acid was positively correlated (r = +0.94**) with sorptivity.